2009
DOI: 10.2337/db08-1240
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exercise Training Does Not Stimulate Skeletal Muscle ATP Synthesis in Relatives of Humans With Type 2 Diabetes

Abstract: OBJECTIVE-We tested the hypothesis that short-term exercise training improves hereditary insulin resistance by stimulating ATP synthesis and investigated associations with gene polymorphisms. RESEARCH DESIGN AND METHODS-We studied 24 nonobese first-degree relatives of type 2 diabetic patients and 12 control subjects at rest and 48 h after three bouts of exercise. In addition to measurements of oxygen uptake and insulin sensitivity (oral glucose tolerance test), ectopic lipids and mitochondrial ATP synthesis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 55 publications
(86 reference statements)
4
72
0
2
Order By: Relevance
“…Furthermore, fATP has been repeatedly shown to be responsive to insulin stimulation, a condition known to increase energy expenditure. The insulin-induced increase in fATP is pronounced in insulin sensitive, but poor or absent insulin resistant states (5,30), again paralleling the response in energy expenditure. This again argues for fATP measurements as markers of oxidative activity.…”
Section: Different Mrs Parameters Of Skeletal Muscle Energy Metabolismmentioning
confidence: 77%
“…Furthermore, fATP has been repeatedly shown to be responsive to insulin stimulation, a condition known to increase energy expenditure. The insulin-induced increase in fATP is pronounced in insulin sensitive, but poor or absent insulin resistant states (5,30), again paralleling the response in energy expenditure. This again argues for fATP measurements as markers of oxidative activity.…”
Section: Different Mrs Parameters Of Skeletal Muscle Energy Metabolismmentioning
confidence: 77%
“…Of note, ex vivo mitochondrial respiration negatively correlates with fasting plasma glucose levels and near-normalization of glycemia by insulin improved respiration in T2DM patients with severe hyperglycemia ( > 15 mmol/l) (61). Recently, we showed that even near-normoglycemic patients with longstanding T1DM show substantial insulin resistance with impaired insulinstimulated myocellular G6P concentrations, as well as compromised mitochondrial plasticity (28) (Fig. 5A and 5B).…”
Section: Glucose-induced Changes In Mitochondrial Plasticitymentioning
confidence: 87%
“…In Non-DM, stimulation by insulin markedly increases myocellular concentrations of substrates for oxidation such as glucose-6-phosphate (G6P) and thereby rates of ATP synthesis (mitochondrial plasticity). In T1DM, both G6P and ATP synthesis do not adequately rise during insulin stimulation (28) . FIG.…”
Section: Effect Of Chronic Hyperlipidemia Associated With Obesitymentioning
confidence: 99%
“…Finally, a variant in the NDUFB6 gene, encoding a subunit of complex I of the respiratory chain, associates with increased type 2 diabetes risk, relates to insulin resistance (48), and predicts the response of muscle energy metabolism to exercise training (16,17). However, no difference in hepatic phosphorous metabolites and HCL between carriers of the A allele in NDUFB6 polymorphism rs540467 and noncarriers was found (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in regulators of oxidative phosphorylation like peroxisome proliferator-activated receptor-g and Δ (genes PPARG and PPARD), PPARG coactivator-1a (gene PPARGC1A), respiratory chain complex 1 (gene NDUFB6), and fat mass-and obesityassociated gene (gene FTO) also modulate glucose and lipid metabolism (14)(15)(16)(17)(18). Several cytokines, such as adiponectin, fetuin A, and fibroblast growth factor 21 (FGF21), can be altered in insulin-resistant states, but also in human (19)(20)(21) and rodent type 1 diabetes (11).…”
mentioning
confidence: 99%